Intestinal permeability in patients with yersinia triggered reactive arthritis. Issue 2 (February 1991) - Lahesmaa-Rantala, R; Magnusson, K E; Granfors, K; Leino, R; Sundqvist, T; Toivanen, A
Abstract : The passive intestinal permeability of patients with yersinia triggered reactive arthritis was studied using different sized polyethylene glycols (PEGs) contained in a mixture of PEG 400 and PEG 1000. The investigation was carried out at least one year after the onset of yersinia infection, and patients had neither acute gastrointestinal nor joint symptoms. The control groups included patients with uncomplicated yersiniosis as well as healthy subjects who were either HLA-B27 positive or negative. An altered intestinal barrier function to PEG molecules was detected in patients with a history of yersinia infection compared with healthy controls. No significant differences in the permeability were found between patients with or without reactive arthritis, nor was there any association of increased permeability with HLA-B27. The passive permeability of the intestinal mucosa to the larger molecules was increased for an unexpectedly long time after the acute yersinia infection, probably contributing to the perpetuation of joint symptoms in subjects susceptible to a chronic joint disease.